Association with Controlling Nutritional Status (CONUT) Score and In-hospital Mortality and Infection in Acute Heart Failure - Takao Kato (Nature Portfolio, 2020)
Abstract The high controlling nutritional status (CONUT) score that represents poor nutritional status has been acknowledged to have prognostic implications in chronic heart failure. We aimed to investigate its role in acute decompensated heart failure (ADHF). Using the data from an multicenter registry that enrolled 4056 consecutive patients hospitalized for ADHF in Japan between 2014 and 2016, we analyzed 2466 patients in whom data on the components of the CONUT score at hospital presentation were available. The decrease of lymphocyte count and total cholesterol was assigned with 0, 1, 2, and 3 points and the decrease of albumin was assigned with 0, 2, 4, and 6 points according to the severity. We defined low CONUT score as 0–4 (N = 1568) and high CONUT score as 5–9 (N = 898). The patients in the high CONUT score group were older and more likely to have a smaller body mass index than those in the low CONUT score group. The high CONUT score group was associated with higher rate of death and infection during the index hospitalization compared to the low CONUT score group (9.0% versus 4.4%, and 21.9% versus 12.7%, respectively). After adjusting for confounders, the excess risk of high relative to low CONUT score for mortality and infection was significant (OR: 1.61, 95%CI: 1.05–2.44, and OR: 1.66, 95%CI: 1.30–2.12, respectively). The effect was incremental according to the score. High CONUT score was associated with higher risk for in-hospital mortality and infection in an incremental manner in patients hospitalized for ADHF.